Dried plum mitigates spinal cord injury‐induced bone loss in mice. Issue 4 (15th July 2020) - Liu, Xuhui; Liu, Mengyao; Turner, Russell; Iwaniec, Urszula; Kim, Hubert; Halloran, Bernard
Abstract: Spinal cord injury (SCI) is accompanied by rapid loss of bone and increased risk of low impact fractures. Current pharmacological treatment approaches have proven to be relatively ineffective in preventing or treating bone loss after SCI. Dietary supplementation with dried plum (DP) has been shown to have dramatic effects on bone in various other disease models. In this study, we tested the efficacy of DP in preventing bone loss after SCI and restoring bone that has already been lost in response to SCI. Male C57BL/6J mice (3‐month‐old) underwent SCI and were fed a diet containing 25% DP by weight or a control diet for up to 4 weeks to assess whether DP can prevent bone loss. To determine whether DP could restore bone already lost due to SCI, mice were put on a control diet for 2 weeks (to allow bone loss) and then shifted to a DP supplemented diet for an additional 2 weeks. The skeletal responses to SCI and dietary supplementation with DP were assessed using microCT analysis, bone histomorphometry and strength testing. Dietary supplementation with DP completely prevented the loss of bone and bone strength induced by SCI in acutely injured mice. DP also could restore a fraction of the bone lost and attenuate the loss of bone strength after SCI. These results suggest that dietary supplementation with DP or factors derived from DP may prove to be an effective treatment for the loss of bone in patients with SCI. Abstract : Spinal cord injury (SCI) is accompanied by rapid loss of bone and increased risk of low impact fractures. In this study, we showed that diet supplement of dried plum (DP) completely prevented bone loss and restored a fraction of the bone lost after SCI in a mouse model. These results suggest that dietary supplementation with DP or factors derived from DP may be an effective treatment for the loss of bone after SCI.